GRUP GAMMA PADA KELAS-KELAS EKUIVALENSI G(S) - Sumanto, Y.D (MATEMATIKA, 2014)
Finite set S with n element can be operated by binary operation. In this paper if is set of binary operation on S that formed as a group, then can be partioned as unintersection classes and every class can be construct as over S.